2019
DOI: 10.3390/insects10080245
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of Long Non-Coding RNAs and Their Regulatory Networks Involved in Apis mellifera ligustica Response to Nosema ceranae Infection

Abstract: Long non-coding RNAs (lncRNAs) are a diverse class of transcripts that structurally resemble mRNAs but do not encode proteins, and lncRNAs have been proven to play pivotal roles in a wide range of biological processes in animals and plants. However, knowledge of expression patterns and potential roles of honeybee lncRNA response to Nosema ceranae infection is completely unknown. Here, we performed whole transcriptome strand-specific RNA sequencing of normal midguts of Apis mellifera ligustica workers (Am7CK, A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 119 publications
5
52
1
Order By: Relevance
“…Besides, the shorter length of the putative lncRNAs and the ORFs compared to mRNA also shared similar features with other well-studied species (Trapnell et al, 2010;Zhang et al, 2014;Wang et al, 2016;Wu et al, 2016;Zhan et al, 2016;Guo et al, 2018a,b;Liu et al, 2019). Although lncRNAs always performed lower expression level than the protein-coding genes (this study; Guo et al, 2018a,b;Chen et al, 2019;Liu et al, 2019), their role in the functional activities of organisms has been widely proved to be of significance (Furuno et al, 2006;Mercer et al, 2009;Zhang et al, 2014;Wu et al, 2016;Chen et al, 2019;Liu et al, 2019).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Besides, the shorter length of the putative lncRNAs and the ORFs compared to mRNA also shared similar features with other well-studied species (Trapnell et al, 2010;Zhang et al, 2014;Wang et al, 2016;Wu et al, 2016;Zhan et al, 2016;Guo et al, 2018a,b;Liu et al, 2019). Although lncRNAs always performed lower expression level than the protein-coding genes (this study; Guo et al, 2018a,b;Chen et al, 2019;Liu et al, 2019), their role in the functional activities of organisms has been widely proved to be of significance (Furuno et al, 2006;Mercer et al, 2009;Zhang et al, 2014;Wu et al, 2016;Chen et al, 2019;Liu et al, 2019).…”
Section: Discussionsupporting
confidence: 84%
“…The present a few studies have demonstrated that these functional elements of lncRNAs participate in the regulation of the physiological processes of honey bees, such as labor division, ovary development, neural networks, pesticide metabolism, and pathogen resistance (Kiya et al, 2008;Humann et al, 2013;Jayakodi et al, 2015;Chen et al, 2017Chen et al, , 2019Liu et al, 2019;Fent et al, 2020). Guo et al (2018a,b) screened the lncRNAs in two honey bee fungi, Ascospheara apis and Nosema ceranae, providing the first two lncRNA profiles in honey bee pathogenic agents.…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies of insect transcriptome analysis have focused on protein-coding genes, and non-coding RNAs were less informative [ 7 ]. According to the genomic location [ 8 ], lncRNAs are classified into four subcategories: long intergenic non-coding RNA (lincRNA), sense lncRNA, anti-sense lncRNA, and intronic lncRNA [ 9 ]. In eukaryotes, lncRNAs are transcribed at several sites of the genome by RNA polymerase II and RNA polymerase III [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNAs identification was widely reported in eukaryote mammals ( Kaushik et al, 2013 ; Zhan et al, 2016 ), plants ( Lv et al, 2016 ), and microorganisms ( Wang Z. et al, 2019 ). In insects, lncRNAs have been investigated in many species ( Zhu et al, 2016 ), e.g., Drosophila Melanogaster ( Wen et al, 2016 ), Apis mellifera ligustica ( Chen D. et al, 2019 ), and Nilaparvata lugens ( Chen M. Y. et al, 2019 ). In this study, only the lncRNAs with a poly “A” tailed were sequenced, so the number of the lncRNAs was less than that in other insects.…”
Section: Resultsmentioning
confidence: 99%